KEEFEKTIFAN SISTEM PENDAFTARAN ONLINE PASIEN RAWAT JALAN RSUP dr. SOERADJI TIRTONEGORO KLATEN - Ana Amirotun Solihah; Savitri Citra Budi (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
The development of various technologies makes easiness in the health field, one of which is the online indirect registration to unravel the patient's buildup due to the length of registration time. Online registration of outpatients applied in RSUP dr. Soeradji Tirtonegoro which is divided into 3 types. However, in the implementation of this system has not been matched by a wise attitude by users, that is the online registration cancellation without confirmation. Therefore, this study aims to determine the implementation and effectiveness of online outpatients registration dr. Soeradji Tirtonegoro. The type of this research is quantitative descriptive with data collection by observation. Implementation procedures online registration RSUP dr. Soeradji Tirtonegoro is described in SPO Outpatient Registration through Short Message Service (SMS) / WhatsApp (WA). From the results of the observation of 1594 sample online registrants, there are positive patients list of 416 applicants via WhatsApp and 1049 registrants via SMS. However, from the sample there are 9 cancellations of registration via WhatsApp and 120 cancellation of registration via SMS. It can be concluded that online registration via SMS has a higher number, both registration and cancellation of registration compared with online registration via WhatsApp